An anisotropic constitutive model for fiber-reinforced materials including gradient-extended damage and plasticity at finite strains. (August 2020) - Holthusen, Hagen; Brepols, Tim; Reese, Stefanie; Simon, Jaan-Willem
Highlights: A transversal isotropic material model formulation is presented. The anisotropic part includes tension–compression asymmetry. Damage and plasticity for the isotropic as well as damage for the anisotropic part are discussed. Gradient-extension is used to avoid artificial mesh-sensitivity. The framework is developed for finite strains. Abstract: An anisotropic, in particular transversal isotropic, thermodynamically consistent material model for unidirectional fiber composite layers at finite strain is proposed. To account for the anisotropy, the concept of structural tensors is used. Tension–compression asymmetric fiber damage as well as an elasto-plastic-damage matrix material are discussed, whereas plasticity and damage are modeled by a two-surface approach. Anisotropic damage is modeled by utilizing three scalar, local damage variables. In this context, mesh-independent damage evolution is achieved using the micromorphic approach presented by [34, 35], separately for the fiber and the matrix part. Further, an element formulation including the additional micromorphic degrees of freedom and its linearization for the global Newton–Raphson scheme are presented. Numerical examples show the behavior of the presented material model at the Gauss point and structural level.